A linguistic analysis of the sample numeracy skills test items for pre-service teachers issued by the Australian Council for Educational Research (ACER). - O'Keeffe, L.; O'Halloran, K.; Wignell, Peter; Tan, Sabine (Australian Association for Research in Education, 2017)
In 2015, the Australian Council for Educational Research (ACER) was tasked with developing literacy and numeracy skills testing for pre-service teachers. All undergraduate and postgraduate trainee teachers are now required to pass these literacy and numeracy tests at some stage on their journey to becoming a teacher; for commencing students from 2017 in all states (except New South Wales), successfully passing these tests is a requirement for graduation. Following this announcement, ACER released a number of sample test items for both literacy and numeracy. This study used multimodal analysis to study the nature of the language, symbolic notation and visual representations in the sample test items for numeracy, with a focus on the linguistic complexity of the questions. The findings suggest that the types of linguistic constructions found in the assessment questions create significant challenges in terms of reading and comprehension which could impact on how the students engage with the numeracy assessment items.